Agricultural sub-sectors in new and updated NDCs: 2020-2021 dataset - Rose, Sabrina; Khatri-Chhetri, Arun; Stier, Milena; Vu, Trang; Nelson, Katherine; Dittmer, Kyle (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Data presented here are the result of an analysis of agricultural sub-sectors within new and updated NDCs. This analysis covers 164 new or updated NDCs submitted as of September 30, 2022. NDCs are available for download at https://www4.unfccc.int/sites/NDCStaging/Pages/All.aspx. This dataset includes information for soil organic carbon and livestock sub-sectors. Information for the rice sub-sector is forthcoming. While every effort has been made to ensure the completeness and accuracy of this data set, please contact S.Rose@cgiar.org and k.dittmer@cgiar.org if you notice any inaccuracies.